Epicardial adipose tissue thickness associated with preeclampsia and birth weight in early pregnancy - Jing Wang; Chunfeng Li; Wen Li; Yexiao Tao; Yong Li (Taylor & Francis Group, 2024)
Objective Preeclampsia (PE) increases the risk of many adverse maternal and fetal outcomes. This study was to investigate the correlation between epicardial adipose tissue (EAT) thickness and PE and birth weight.Methods This was a single-center retrospective study, 221 patients with PE were selected, and 81 women without hypertension and proteinuria were selected as a comparison. Echocardiogram was performed in their first prenatal examinations at 11-13 gestational weeks, and the thickness of EAT was measured. At the subsequent follow-up, the birth weight was recorded.Results EAT thickness was significantly elevated (6.60 ± 1.34 vs. 5.71 ± 1.79 mm, p < 0.001) in severe PE compared to mild PE. In the multivariate analysis, EAT thickness (OR 5.671, 95% CI, 1.991-16.150, p = 0.001), and C reactive protein (OR 4.097, 95% CI, 2.323-7.224, p < 0.001) were found as significant independent predictors of severe PE after adjusting for other risk factors. Linear regression analysis showed that hs-CRP, EAT thickness, and severe PE significantly negatively affected birth weight.Conclusion EAT thickness can be used to identify pregnant women with severe PE risks and low birth weight. It is an independent risk factor for severe PE but is not a valuable sign of mild PE.